Reforming New South Wales public hospitals: an assessment of the Garling inquiry - Skinner, Clare A; Braithwaite, Jeffrey; Frankum, Brad; Kerridge, Ross K; Goulston, Kerry J (Medical journal of Australia, 2009)
The final report of the Special Commission of Inquiry into Acute Care Services in NSW Public Hospitals was published on 27 November 2008. The report acknowledges the challenges facing the New South Wales health system, including increasing numbers of patients, rising treatment costs, workforce pressures, and the breakdown of working relations between clinicians and management. Many of Commissioner Garling's 139 recommendations formalise aspects of clinical care that should and could be happening now if the system were better managed, including better supervision and training of junior staff. Commissioner Garling recommends that change should be driven by clinicians “from the bottom up”, but does not adequately describe how this should happen. Implementation of the report's recommendations that will require strong leadership and continuing consultation with clinicians and the community.